On the electoral relevance of education policy in the German Länder - Wolf, Frieder; Krämer, Andreas (German politics, 2012)
Education policy in Germany experienced a boom throughout the 2000s. Numerous reforms were implemented, quite far-reaching shifts of party programmes occurred, and the scope of institutions with an educational mandate widened considerably. At the same time, Landtag elections came to be seen as less dominated by federal politics. Yet we still know little about education policy's electoral relevance. The present article, following a most-likely design, analyses those five Landtag elections that were held since the reform of federalism in 2006 for which the importance of education policy ought to have been highest. It turns out that even though education is one of the very few policies which the Länder can decide upon autonomously, and despite the recent upsurge of regional factors in determining the outcomes of such second-order elections, nearly all Landtag elections are won or lost on other battlefields.